Generation and precise control of sulfonyl radicals: visible-light-activated redox-neutral formation of sulfonates and sulfonamides. Issue 5 (12th January 2021) - Zhang, Mingjun; Ding, Xin; Lu, Aidang; Kang, Jin; Gao, Yongyue; Wang, Ziwen; Li, Hongyan; Wang, Qingmin
Abstract : An efficient protocol to direct sulfonamidation or sulfonation of electron-deficient alkenes for furnishing alkylsulfonamides or sulfonates has been achieved. Abstract : The sulfonamidation or sulfonation of electron-deficient alkenes is the most direct way to furnish alkylsulfonamides or sulfonates, which are of importance for the discovery of new bioactive molecules in medicinal research. Herein we report a protocol for the generation and precise control of the sulfonyl radical from dimethylsulfamoyl chloride. Different kinds of alkyl sulfonates and sulfonamides were efficiently and selectively obtained under redox-neutral conditions by controlling the reactivity of photocatalysts. A mechanism for the generation of sulfamoyl and sulfonate radicals from dimethylsulfamoyl chloride and the followed sulfonation and sulfonamidation are proposed. This reaction system offers a distinct advantage over traditional oxidation or reduction sulfonation methods in not requiring the use of sulfur dioxide, sulfonic acid, a stoichiometric reductant, or a stoichiometric oxidant. Thus, it should be of practical value for the late-stage functionalization of natural products or medicines.